Sustainability through directed change in the visionary university: From predicting to producing the future - Adrian Curaj; Mihai Păunică; Andreea Popa; Cosmin Holeab; Octavian-Dragomir Jora (Amfiteatru Economic Journal, 2020)
The sustainability of a university can be questioned from the perspective of three functional goals, henceforth setting the analytical framework: (i) the development of suited knowledge (dynamic and evolving, mirroring the complexity of the socioeconomic environment, definitely internationalised and future-oriented), (ii) the development of students' skills, as future workforce (valuing the knowledge) and (iii) the development of institutional capacities, in agile constructions (adequate to face the first two challenges). Such a vision of sustainability in higher education treats change as the very "fuel" of sustainability, not as a threat, an ordeal, or a risk factor; it also transfers the notion of "being sustainable" from an attribute of a state to that of a process; and at the same time, it is precisely a process that does not simply "happen", but is purposefully driven by action, and it comprises a multi-level and polyvalent reality, where prognosis is to be accompanied by proactivity, forecast by foresight, and piecemeal approaches by systemic ones. This essay thoroughly contextualizes such a conceptualization of the sustainable university. It aims to identify some problems that higher education encounters in the managerial, teaching and research processes, that is in the creation and transfer of knowledge, within the current international institutional setup. It also seeks to explain how a culture of collaboration can be developed in such a way that good practices and knowledge are to be shared, obstacles are to be overcome, and efforts are to be capitalized upon in this context. It is essential to understand how teachers, students and graduates can all become prepared to muster and master such change, instead of being led by it or becoming its victims, governing both normalcy and disruptions. It also outlines a strategic understanding and a performance "kit" with innovative approaches, tools and other resources for universities aspiring to carry out plenary sustainability; thence, even if this logic might (not) have been tried out within present-day Romanian higher education, it should be part of its future tense.
Keywords: I23; I25; O33; O34; O36; F53; F55; 330; higher education; sustainable development; globalization; change; technology; management; leadership